2017
DOI: 10.17015/ejbe.2017.019.05
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Economic Growth in Syria between 1980 and 2010

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…They concluded that these four factors have a positive effect on economic growth. Mohsen et al (2017) investigated the determinants of Syrian economic growth using data in the period 1980-2010. The variables observed were public sector investment, private sector investment, export, oil prices and population growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that these four factors have a positive effect on economic growth. Mohsen et al (2017) investigated the determinants of Syrian economic growth using data in the period 1980-2010. The variables observed were public sector investment, private sector investment, export, oil prices and population growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A country's exports play an important role in promoting economic growth. Exports can supply the state budget through income and foreign currencies which can be used to improve infrastructure and create an attractive investment climate [2]. In addition, exports also have an important role in developing domestic product markets.…”
Section: Introductionmentioning
confidence: 99%